Sistematização da Assistência de Enfermagem em unidade básica de saúde: percepção da equipe de enfermagem - Ribeiro, Grasielle Camisão; Padoveze, Maria Clara (Revista da Escola de Enfermagem da USP, 2019)
Objective: To conduct a situational diagnosis of the Nursing Care Systematization (NCS) in a Basic Health Unit from the perception of the nursing team. Method: This was a quantitative, descriptive-exploratory study, conducted in a Basic Health Unit in the interior of São Paulo state, Brazil. A structured questionnaire containing Likert scale was used for data collection, previously validated by specialists. Results: The questionnaire was applied to 21 nursing professionals. It was verified that implementation of NCS and the nursing process is still incipient in the Basic Health Units. Regarding its use in all nursing actions: 19% of respondents believe that it is never used, 38% thought that it is rarely implemented, and 29% responded sometimes. The main difficulties identified were related to the lack of institutional structure, highlighting a lack of capacity by the institution (81%). The team has a reasonable understanding about the subject, but pointed out that professional education does not prepare them for performing NCS in primary care. Conclusion: Institutional interest in NCS is necessary to enable implementation. The study can contribute to the effective implementation in this unit and point out guidelines for its implementation in other similar contexts.